Challenging the perceptions of cancer service provision for the disadvantaged: evaluating utilisation of cancer support services in Western Australia - Moorin, Rachael; Gibson, D.; Bulsara, C.; Holman, C. (Springer, 2012)
Purpose: The main aim of the study was to evaluate the distributive utilisation of services provided by the Cancer Council of Western Australia according to age, social disadvantage and geographic location. Results were used to determine if social justice principles in terms of service provision were upheld. Methods: Cross-sectional study design to evaluate utilisation of cancer support services over a 12-week period in 2007 using administrative records. Service utilisation incidence rates (population information obtained from de-identified cancer registry data) and incidence rate ratios were calculated by gender, age group, cancer type, socioeconomic status and location. Results: The Information services (52%, n = 4,932) were the most popular Cancer Council of Western Australia (CCWA) services followed by Emotional Support services (21%, n =  2,045). All CCWA services were more likely to be accessed by those with a lower socioeconomic status, except for Clinical Services. The rate of utilisation for patients with cancer in the 65+ years age group was found to be under-serviced relative to the 40–64 years age group. Conclusions: Overall, the study has shown that CCWA services are not provided uniformly (horizontal equity) across strata of socio-economic status. Given that the prevalence of cancer generally increases with socio-economic advantage, the findings were notable in regard to one particular outcome. Results for age indicate that there may be some underlying accessibility issues for the aged population. The findings are consistent with current literature highlighting issues of disadvantage in regard to the ability of elderly persons with cancer to access services and support.